CTA Project Completion Report: D4Ag report - Addom, Benjamin K.; Kermah, Michael; Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2020)
Working together with Dalberg Advisors, CTA published The Digitalisation of African Agriculture Report in June 2019 (the publication can be downloaded from https://tinyurl.com/y6546zwh). This was a “first-of-its-kind”, baseline report that highlights the state of digitalisation in enabling the transformation of African agriculture. The report was distributed through different channels – and reached thousands of readers in Africa and elsewhere. Several months later, CTA conducted this study to assess if the objectives of the report had been achieved. CTA was specifically interested in seeing how the report had been or is being used, and the extent to which the recommendations of the report have been or are being implemented. Next to this, CTA wanted to see if there is a general interest in building upon this work; and thereby generate targeted recommendations for any future actions by those stakeholders wishing to build on CTA’s legacy.